Phenology of Leaf Flushing, Flower Initiation and Fruit Maturation in Dry Deciduous and Evergreen Forests of Bhadra Wildlife Sanctuary, Karnataka, Southern India - Nanda, A.; Prakasha, H.M.; Krishna Murthy, Y.L.; Suresh, H.S. (Our Nature, 2012)
Varying with altitude and rainfall of two forest types of tropical forest were studied. Community wide pattern in both vegetative and reproductive phenophases among various tree species of Bhadra wildlife sanctuary, Karnataka is reported here. Leaf initiation peaks in the month of April in dry forest, after leaf less period of 1-2 months, in evergreen forest leaf initiation peaks in the month of January simultaneously with leaf senescence. Flower initiation begins from January till June with a peak in April in dry forest. Evergreen forest starts from November to march with a peak in January and February. Fruit maturation in dry forest starts from March to December with a peak in August and November, in evergreen forest from January to July with a peak in April. DOI: http://dx.doi.org/10.3126/on.v9i1.5738